Conceptual framework for health-preserving activities in educational organisations within the context of quality management - V. A. Fedorov; N. V. Tretyakova (Russian State Vocational Pedagogical University, 2023)
Introduction. The negative dynamics of the reduction in the total number of children and the increase in their incidence in the world and federal space require the solution of problems to preserve the health of the child population within the framework of the education system. Education is the only system of public education, where almost the entire child population is covered for a long time. Despite the many studies and aspects of the activities of educational organisations in the field of students' health preservation, there is no need to talk about the large-scale effectiveness of this activity.Aim. The aim of the study is to reveal the conceptual framework of the activities of educational organisations for the protection of students' health in the context of the theory of quality management, based on the integration of existing experience, its rational organisation and management.Methodology and research methods. The methodological basis for the construction of the concept was the process and system approaches. The application of these approaches made it possible to substantiate the proposed 1) targets for the activities of educational organisations in the field of students' health preservation; 2) structural transformations within the educational organisation; 3) principles and requirements for the management process. The experimental search base of the study involved 14 general educational organisations and organisations of secondary vocational education of the Ural region, the total number of participants - 7,210. The authors used the general scientific methods of generalisation, comparison, synthesis and analysis to carry out an interdisciplinary analytical review of the problem field of the study.Evaluation of the effectiveness of the implementation of the concept was carried out according to the authors' system of criteria, which corresponds to the structure of the components of the quality of health care activities (quality of conditions, quality of processes and quality of results). To confirm the reliability of the results of the study, student's t-criterion was used; to identify dependencies, the authors applied the method of correlation analysis (according to Pearson).Results and scientific novelty. In the course of the study, the authors resolved the contradiction between the needs of society and man in achieving the effectiveness of the activities of educational organisations to preserve the health of students and the possibilities of the education system to ensure the implementation of these needs, since the conceptual provisions of the activities of educational organisations in health care in the context of the theory of quality management have not been developed. At the same time, the issues of organisation and management of this activity have been resolved. The scientific novelty of the study is the developed and tested concept: 1) the target and result of health protection activities is the formation and level of readiness of students to maintain health; 2) the management of the activities of educational organisations in health care is based on the theory of quality management, which requires the implementation of the ideas of the process approach and reflected in the authors' management principles; 3) the level of organisation of health activities depends on the degree of structuring of its main directions; this requires the creation of a specialised division at the expense of the internal resources of the educational organisation - the health service; 4) the main objects of management are the quality of conditions, the quality of processes and the quality of the results of health care activities, which have become the basis of the system of criteria for its comprehensive assessment; 5) the effectiveness of the implementation of the concept depends on ensuring that the needs of the main actors in health care are constantly taken into account, its continuous improvement with the leading role of management, orientation to the key goal the formation of students' readiness to maintain health, and the inclusion of all participants of the educational process in health protection.Practical significance. The application of the ideas of the concept can become the basis for the innovative development of the activities of educational organisations in the field of students' health preservation, and can determine the directions for solving fundamental and applied problems of this type of educational activity.